Analysis of the Effect of Population on Unemployment in West Lombok Regency 2012-2021 - Aminy, Muhammad Habibullah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research is entitled "Analysis of the Effect of Population on Unemployment in West Lombok Regency 2012-2021". In this study, researchers wanted to see how the population compared to unemployment in West Lombok Regency from 2012-2021. This type of research is quantitative research with an associative approach. The analytical tool used in this research is simple linear regression analysis. The results of this research are an R-square value of 0.545 with a significance value (α) or alpha of 0.05 (5%). The R-square value in this study has meaning, namely that the influence of the population variable is able to explain the unemployment variable in West Lombok Regency by 54.5%. That is, partially the influence of the independent variable population size on unemployment in West Lombok Regency is not significant. This is indicated by the calculated T value being greater than the T table value. T calculated < T table (T calculated 0.737 > T table 2.306).